PENGEMBANGAN STRATEGI PEMBELAJARAN BERBASIS NILAI KRISTEN UNTUK MENANGGAPI TANTANGAN BUDAYA KONTEMPORER - Novita Sapan; Seprianti, Ravika, Jeni Tandi Limbong (CV. ADIBA AISHA AMIRA, 2025)
This research aims to develop a Christian values-based learning strategy that is responsive to the challenges of contemporary culture in Christian educational environments. Through a holistic approach encompassing literature review and qualitative analysis, this study focuses on aligning Christian values with the dynamics of contemporary culture. The literature review provides a profound theoretical foundation, identifying effective approaches to integrate Christian values into education. Qualitative analysis involves case studies with stakeholders, enabling a deep understanding of the challenges and dynamics of contemporary culture in Christian educational settings. The findings of this research are expected to contribute to the development of a learning strategy that emphasizes the formation of students' character and the application of Christian values in navigating evolving cultural changes. Thus, this study provides a solid foundation for the development of relevant and responsive Christian education to meet the challenges of contemporary culture.